Question

\( x^{2}-5 x y+y^{2}=7 \) and \( x-4 y=5 \)

Ask by Mann Nichols. in South Africa
Feb 20,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The solutions are \( (x, y) = (1, -1) \) and \( (x, y) = (29, 6) \).

Solution

Solve the system of equations \( x^{2}-5x*y+y^{2}=7;x-4y=5 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}x^{2}-5xy+y^{2}=7\\x-4y=5\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x^{2}-5xy+y^{2}=7\\x=5+4y\end{array}\right.\) - step2: Substitute the value of \(x:\) \(\left(5+4y\right)^{2}-5\left(5+4y\right)y+y^{2}=7\) - step3: Simplify: \(25+15y-3y^{2}=7\) - step4: Move the expression to the left side: \(25+15y-3y^{2}-7=0\) - step5: Subtract the numbers: \(18+15y-3y^{2}=0\) - step6: Factor the expression: \(3\left(6-y\right)\left(1+y\right)=0\) - step7: Divide the terms: \(\left(6-y\right)\left(1+y\right)=0\) - step8: Separate into possible cases: \(\begin{align}&6-y=0\\&1+y=0\end{align}\) - step9: Solve the equation: \(\begin{align}&y=6\\&y=-1\end{align}\) - step10: Calculate: \(y=6\cup y=-1\) - step11: Rearrange the terms: \(\left\{ \begin{array}{l}x=5+4y\\y=6\end{array}\right.\cup \left\{ \begin{array}{l}x=5+4y\\y=-1\end{array}\right.\) - step12: Calculate: \(\left\{ \begin{array}{l}x=29\\y=6\end{array}\right.\cup \left\{ \begin{array}{l}x=1\\y=-1\end{array}\right.\) - step13: Calculate: \(\left\{ \begin{array}{l}x=1\\y=-1\end{array}\right.\cup \left\{ \begin{array}{l}x=29\\y=6\end{array}\right.\) - step14: Check the solution: \(\left\{ \begin{array}{l}x=1\\y=-1\end{array}\right.\cup \left\{ \begin{array}{l}x=29\\y=6\end{array}\right.\) - step15: Rewrite: \(\left(x,y\right) = \left(1,-1\right)\cup \left(x,y\right) = \left(29,6\right)\) The solutions to the system of equations \(x^{2}-5xy+y^{2}=7\) and \(x-4y=5\) are \((x,y) = (1,-1)\) and \((x,y) = (29,6)\).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Beyond the Answer

To solve the system of equations given by \( x^{2}-5xy+y^{2}=7 \) and \( x-4y=5 \), you can start by expressing \( x \) in terms of \( y \) using the second equation: \( x = 4y + 5 \). Substitute this expression for \( x \) into the first equation, yielding a quadratic in terms of \( y \). This will allow you to solve for \( y \), and subsequently use the found values to determine corresponding \( x \) values. Now, a common mistake in these types of problems is neglecting to check if both solutions for \( y \) lead to valid values for \( x \) in the first equation. Always substitute both back into the original equations to ensure they hold true, which makes for a safer mathematical journey!

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy